Potato minituber production by aeroponics: Effects of genotype and plant origin - Oljača Jasmina M.; Broćić Zoran A.; Pantelić Danijel I.; Rudić Jelena J.; Poštić Dobrivoj Ž.; Momčilović Ivana D. (Journal of Agricultural Sciences (Belgrade))
Aeroponics is a modern farming technology for soilless potato cultivation that enables the efficient production of high-quality pre-basic seed potatoes (minitubers). In this system, the roots and underground stems (stolons) of the potato plants grow within closed modules, suspended in a fine mist of a nutrientrich solution that continuously recirculates. This setup enables the formation of numerous minitubers with a length greater than 10 mm during the growing period. Our study aimed to evaluate the impact of the genotype and origin of the planting material on minituber production in an aeroponic facility in Guča, Serbia. Three potato cultivars were analyzed: Cleopatra, Kennebec, and Désirée, using two types of planting material: acclimated microplants and plants derived from the previous season's minitubers. The plants were cultivated aeroponically from late May to December 2019, with a planting density of 24 plants per square meter and harvest intervals of approximately 14 days. The Désirée cultivar produced the highest average number of minitubers per plant (19.89), followed by Kennebec (15.71) and Cleopatra (11.05). The average weight of minitubers was significantly greater in plants grown from last season's minitubers compared to plants grown in vitro. The Kennebec plants originating from minitubers achieved the highest yield of 10.27 kg per square meter. Additionally, the plants originating from minitubers consistently produced tubers throughout the entire cultivation period in the aeroponic growing system.